Significant applications of digital modeling in the construction sector for improving project management and performance - Aldhamad, Saja Hadi Raheem; Zaki, Rana I. K.; Al-Zwainy, Faiq M. S.; Varouqa, Ibrahim Farouq; Obaid, Aseel H. (Edelweiss Applied Science and Technology, 2025)
The purpose of the digital models is to aid users in better understanding the response and behavior of the construction management system under different conditions. The main advantage of the digital models lies in the ability to use possible alternatives and analyze the effect of various factors on the project management system, both before and during performance. This study will review previous works. Types of BIM and simulation techniques are discussed, along with the reasons for using this technique, its applications, and characteristics in the construction sector. The application of digital models in the construction sector is also reviewed. The research concludes that simulation modeling has a revolutionary impact on construction project management, as it provides advanced tools for planning efficiency, resource allocation, cost calculation, sustainability, and risk management. While obstacles such as the requirement for skilled personnel and the integration with existing systems remain, the benefits of simulation modeling in terms of cost savings, improved efficiency, and more effective decision-making make it an essential aid for construction projects.